A re-examination of the effects of the economy, government spending, and incumbent ideology on national policy mood. (December 2015) - Kim, HeeMin; Yoo, Hyeyoung; Roh, Jungho
Previous explanations of the causes of shifts in policy mood have been primarily economic. When the economy expands aggregate policy preferences move left, but when the economy contracts aggregate policy preferences move right. In this paper, we seek to improve our understanding of the causes of national policy mood shift in two ways. First, we focus on government spending and its impact on policy mood. Previously scholars used it as a control variable in their models and pretty much assumed that intrusive spending will move policy mood to the right, while lack of it will move policy mood to the left. We investigate if different types of the spending have different effects on the policy mood of a nation. Second, we seek a better understanding of the impact of national economic conditions on policy mood by looking at more countries, using various data and more sophisticated methodology. A panel data analysis of two different measures of the policy mood, one based on party manifestos (24 countries and 33 years) and the other based on voter surveys (17 countries and 29 years), reveals that: (i) there is ample evidence that economic conditions have a direct impact on the policy mood of citizens; (ii) the national policy mood is generally negatively related to the current government ideology; (iii) an expanding economy pushes policy mood to the left when the incumbent's ideology is moderate to rightist; (iv) failure to control inflation causes aggregate policy preferences to shift to the right only under a moderate to left-leaning government; (v) failure to control unemployment causes national policy preferences to shift to the right only under a moderate to right-leaning government; (vi) increasing social spending pushes policy mood further to the left only under a moderate to left-leaning government; and (vii) increasing military spending pushes policy mood to the left only under a moderate to left-leaning government.